Vietnamese government scales agroclimatic bulletins across 13 provinces in the Mekong Delta, reaching more than 290,000 farmers - Le, Tam Thi; Swaans, Cornelis (2025)
An evaluation conducted in 2024 showed the Vietnamese government successfully scaled agroclimatic bulletins (ACBs) from 7 to 13 provinces in the Mekong River Delta (MRD), reaching 291,494 farmers, without additional funding from the Asian Mega-Deltas (AMD) initiative. The increase in the number of farmers was marked by the expansion in districts and communes, as well as the inclusion of more crops.